Nebulizer Care and Inhalation Technique in Children with Cystic Fibrosis - Argyri Petrocheilou; Athanasios G. Kaditis; Evgenia Troupi; Ioanna Loukou (Children, 2020)
Nebulizers are used by the great majority of cystic fibrosis patients for delivery of cornerstone treatments. Inhalation technique and adequate disinfection and maintenance are important for optimizing medication delivery. In this study, inhalation technique and nebulizer disinfection/maintenance were assessed in cystic fibrosis patients by direct observation in clinic and completion of a scoring sheet. A total of 108 patients were recruited. The maximum inhalation technique score was attained by 30.5% and adequate inhalation technique score by 74.08% of patients. The inhalation technique score was best with the vibrating mesh nebulizer (p = 0.038), while patient age and number of nebulized medications did not affect ITS significantly (p > 0.05). Nebulizer disinfection/maintenance score was excellent in only 31.48%. Most families kept the nebulizer clean and used appropriate disinfection method, but only half of them replaced the nebulizer and nebulizer cup at the recommended time intervals. Nebulizer disinfection/maintenance score was positively affected by a number of nebulized medications and negatively by years of equipment use (p = 0.009 and p = 0.001, respectively). Even though inhalation technique and disinfection/maintenance practices were found to be adequate in a large proportion of cases, there is still a need for regular review and education. The type of nebulizer was associated with improved inhalation technique, but more data are required before making specific recommendations.